Caffeic acid: an antioxidant with novel antisickling properties. Issue 12 (22nd September 2021) - Kassa, Tigist; Whalin, James G.; Richards, Mark P.; Alayash, Abdu I.
Abstract : It is well documented that caffeic acid (3, 4‐dihydroxycinnamic acid) (CA) interacts with and inhibits the oxidative reactions of myoglobin (Mb) and hemoglobin (Hb), and this interaction underlies its antioxidative action in meat. Sickle cell hemoglobin (HbS) is known for its tendency to oxidize more readily than normal HbA in the presence of hydrogen peroxide (H2 O2 ), which leads to a more persistent and highly oxidizing ferryl Hb (HbFe 4+ ). We have investigated the effects of CA on HbS oxidation intermediates, specifically on the ferric/ferryl forms. At a low concentration of H2 O2 (0.5‐fold over heme), we observed a fivefold reduction in the amount of HbFe 4+ accumulated in a mixture of ferric and H2 O2 solution. Higher levels of H2 O2 (onefold and twofold over heme) led to a lesser threefold and twofold reduction in the content of HbFe 4+, respectively, possibly due to the saturation of the binding sites on the Hb molecule. The most intriguing finding was that when 5‐molar excess CA over heme was used, and a considerable increase in the delay time of HbS polymerization to approximately 200 s was observed. This delay in polymerization of HbS is theoretically sufficient to avoid microcapillary blockage and prevent vasoconstrictions in vivo . Mass spectrometry analysis indicated that CA was more extensively covalently bonded to βCys 93 than to βCys 112 and αCys 104 . The dual antioxidant and antisickling properties of CA may be explored further to maximize its therapeutic potential in SCD. Abstract : Caffeic acid (CA) is known for its antioxidant effects. The underlying mechanism of its action reported here includes reduction in the content of the highly reactive sickle cell ferryl Hb. CA also exhibited a novel antisickling effect by increasing the delay time before polymerization of HbS. Mass spectrometric analysis of the reaction reveals that CA covalently binds to the hot spot βCys93.